Upaya Peningkatan Pemahaman Materi Mata Kuliah Matematika Dengan Menerapkan Pilar-Pilar CTL (Contextual Teaching And Learning) Pada Mahasiswa S1 PGSD Pokjar Kota Madiun. (Kajian Konseptual) - Tresnaningsih, Sri (JURNAL AGRI-TEK, 2015)
Students Elemantery Education Universitas Terbuka (UT) in Madiun includes students PGSD and PGPAUD. For S-1 PGSD is input D-2 PGSD and high school backgrounds of various inputs such as from high school science, high school social studies, vocational school with a variety of majors. Clumps mathematics courses listed in the curriculum of UT are in the 2nd half, 3.4 and 8. Mathematics with code PDGK 4108 consists of 12 modules contains more high school math material. Being material to SD's more widely discussed in the module Mathematics Education I, II modules Mathematics Education and Learning Mathematics in Elementary School. Research on